The influence of the ‘threshing board’ sites on the Meseta Palaeolithic record. An ethnoarchaeological approach - Álvarez Alonso, David; de Andrés Herrero, María (Complutum, 2011)
This paper analyzes the problem of the many archaeological assemblages found in the Castilian Meseta and created by the recent and contemporary activity of threshing cereals using wooden boards with stone tools (‘trillero’), which can be misinterpreted as of Palaeolithic age. The process of threshing using quartzite stones is systematically described, as well as the knapping technology used to make the cutting tools and the geological and archaeological formation of the assemblages.